2014
DOI: 10.1111/jnc.12967
|View full text |Cite
|
Sign up to set email alerts
|

P301L tau expression affects glutamate release and clearance in the hippocampal trisynaptic pathway

Abstract: Individuals at risk of developing Alzheimer’s disease (AD) often exhibit hippocampal hyperexcitability. A growing body of evidence suggests perturbations in the glutamatergic tripartite synapse may underlie this hyperexcitability. Here, we used a tau mouse model of AD (rTg(TauP301L)4510) to examine the effects of tau pathology on hippocampal glutamate regulation. We found a 40% increase in hippocampal vGLUT, which packages glutamate into vesicles, and has previously been shown to influence glutamate release, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
99
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(111 citation statements)
references
References 83 publications
(110 reference statements)
11
99
1
Order By: Relevance
“…The present study extends our previous finding that riluzole rescues the detrimental glutamate dysregulation observed in mice expressing P301L mutant tau (Hunsberger et al 2014a; Hunsberger et al 2015). Here, we have demonstrated that TauP301L mice exhibit larger glutamate transients, primarily due to differences in amplitudes.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The present study extends our previous finding that riluzole rescues the detrimental glutamate dysregulation observed in mice expressing P301L mutant tau (Hunsberger et al 2014a; Hunsberger et al 2015). Here, we have demonstrated that TauP301L mice exhibit larger glutamate transients, primarily due to differences in amplitudes.…”
Section: Discussionsupporting
confidence: 90%
“…Our previous work suggests that TauP301L mice exhibit an increase in potassium-evoked glutamate release, as well as a decrease in glutamate uptake (Hunsberger et al 2014a; Hunsberger et al 2015). These results are coupled with changes in neuronal proteins, including an increase in the vesicular glutamate transporter responsible for packaging glutamate into vesicles and shown to mediate glutamate release (Moechars et al 2006; Wilson et al 2005), and a decrease in glutamate uptake transporter (GLT-1) expression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…By analogy, microglial pro-inflammatory cytokines can trigger Tau pathology via reactive oxygen species and thus contribute to disease progression [23,39]. Elevated levels of the extracellular neurotransmitter and excitotoxin glutamate were reported in the hippocampus of mutant Tau mice [24]. The question still remains whether these findings represent a cause or an effect of the Tau alterations.…”
Section: Prion-like Mechanism Of Spreadingmentioning
confidence: 96%